Prediction of Sustained Virological Response to Telaprevir-Based Triple Therapy Using Viral Response within 2 Weeks. (28th September 2014) - Tamai, Hideyuki; Shimizu, Ryo; Shingaki, Naoki; Mori, Yoshiyuki; Maeshima, Shuya; Nuta, Junya; Maeda, Yoshimasa; Moribata, Kosaku; Muraki, Yosuke; Deguchi, Hisanobu; Inoue, Izumi; Maekita, Takao; et al.
Abstract : The aim of the present study was to predict sustained virological response (SVR) to telaprevir with pegylated interferon (PEG-IFN) and ribavirin using viral response within 2 weeks after therapy initiation. Thirty-six patients with genotype 1 hepatitis C virus (HCV) and high viral load were treated by telaprevir-based triple therapy. SVR was achieved in 72% (26/36) of patients. Significant differences between the SVR group and non-SVR group were noted regarding response to prior PEG-IFN plus ribavirin, interleukin (IL)28B polymorphism, amino acid substitution at core 70, cirrhosis, hyaluronic acid level, and HCV-RNA reduction within 2 weeks. Setting 4.56 logIU/mL as the cut-off value for HCV-RNA reduction at 2 weeks, the sensitivity, specificity, positive predictive value, negative predictive value, and accuracy for predicting SVR were 77%, 86%, 95%, 50%, and 79%, respectively, and for neither the IL28B minor allele nor core 70 mutant were 80%, 71%, 91%, 50%, and 78%, respectively. In conclusion, evaluation of viral reduction at 2 weeks or the combination of IL28B polymorphism and amino acid substitution at core 70 are useful for predicting SVR to telaprevir with PEG-IFN and ribavirin therapy.